1992
DOI: 10.1002/j.1460-2075.1992.tb05285.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential splicing of the GHF1 primary transcript gives rise to two functionally distinct homeodomain proteins.

Abstract: The POU domain protein GHF‐1 has a critical role in generation, proliferation and phenotypic expression of three pituitary cell types. GHF‐1 functions in part by binding to and transactivating the promoters of both the growth hormone (GH) and prolactin (PRL) genes and that of the GHF1 gene itself. We describe a naturally occurring isoform of GHF‐1, GHF‐2, in which an additional 26 amino acids are inserted into the activation domain of the protein as a result of alternative splicing. GHF‐2 retains the DNA bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 57 publications
(119 reference statements)
5
91
1
Order By: Relevance
“…The function of POU1F1-β variant has been analysed by other authors. Morris et al (1992), Konzak and Moore (1992) and Theill et al (1992) agreed that, similarly to our results, the rat β variant has only 5 to 10% of the Wt capacity to trans-activate the PRL promoter. In agreement with our results, Haugen et al (1994) observed that, in HeLa cells, the β variant stimulated GH promoter but had almost no effect on PRL promoter.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The function of POU1F1-β variant has been analysed by other authors. Morris et al (1992), Konzak and Moore (1992) and Theill et al (1992) agreed that, similarly to our results, the rat β variant has only 5 to 10% of the Wt capacity to trans-activate the PRL promoter. In agreement with our results, Haugen et al (1994) observed that, in HeLa cells, the β variant stimulated GH promoter but had almost no effect on PRL promoter.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our results, Haugen et al (1994) observed that, in HeLa cells, the β variant stimulated GH promoter but had almost no effect on PRL promoter. When both isoforms are co-expressed, contradictory results were described: Theill et al (1992) and Vila et al (1993) observed a dominant negative repressor effect of the β variant, while Konzak and Moore (1992) observed that Wt and β are not antagonists, they can function together and interact in the activation of the rat PRL promoter when co-expressed, in agreement with the results of the present work. Diamond and Gutierrez-Hartmann (2000) stated that, in pituitary cell lines, POU1F1-β represses PRL promoter, but in non-pituitary cells, like HeLa cells, the rat β variant presented a higher capacity to activate PRL promoter.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Recently an alternative splicing variant of Pit-1 called Pit-1a, Pit-1/3, or GHF-2 has been reported [24][25][26]. This splicing variant has 26 amino acid insertions in the transactivation domain of the original Pit-1.…”
Section: Discussionmentioning
confidence: 99%